A case report of traumatic ulcerative granuloma with stromal eosinophilia (TUGSE) in a 21‐year‐old. Issue 11 (9th September 2020) - Hannan, Tufayl Ahmed; Umer, Muhammed; Syed, Labib; Anis‐Alavi, Mohamed Areeb
Abstract: We present an unusual case of a persistent solitary left palatoglossal ulcer with no history of trauma or associated risk factors. A TUGSE lesion, which mimics that of malignancy, must always be noted as a differential even in risk factor absence. Abstract : We present an unusual case of a persistent solitary left palatoglossal ulcer with no history of trauma or associated risk factors. A TUGSE lesion, which mimics that of malignancy, must always be noted as a differential even in risk factor absence.